Integration of mechanical and chemical signals by YAP and TAZ transcription coactivators - Guo, Xiaocan (BioMed Central, 2013)
YAP and TAZ are transcription coactivators and effectors of the Hippo pathway, which play a key role in organ size control. Through interaction with transcription factors such as TEADs, they activate gene transcription and thus promote cell proliferation, inhibit apoptosis, and regulate cell differentiation. Dysregulation of YAP/TAZ was found to correlate with human cancers. The oncogenic roles of these proteins were also demonstrated in animal models. The growth promoting activity of YAP/TAZ is limited by the Hippo tumor suppressor pathway through phosphorylation-induced cytoplasmic retention and destabilization. Recently, it was found that YAP and TAZ mediate responses to several extracellular signals including mechanical stress, GPCR signaling, and the Wnt signaling pathway. All these growth-regulating signals play important roles in normal development and cancer. In this review, we would like to discuss the function of YAP and TAZ as effectors of these physiological signals.